Pediatric Cerebral Palsy in Africa: A Systematic Review - Donald, Kirsten A.; Samia, Pauline; Mwesige, Angelina Kakooza; Bearden, David (WB Saunders, 2014)
Cerebral palsy is a common neurologic problem in children and is reported as occurring in approximately 2-2.5 of 1000 live births globally. As is the case with many pediatric neurologic conditions, very little has been reported on this condition in the African context. Resource-limited settings such as those found across the continent are likely to result in a different spectrum of etiologies, prevalence, severity as well as management approaches. This review aims to establish what has been reported on this condition from the African continent so as to better define key clinical and research questions.